Limnology and trophic status of glacial lakes in the tropical Andes (Cajas National Park, Ecuador). (9th December 2016) - Van Colen, Willem R.; Mosquera, Pablo; Vanderstukken, Maarten; Goiris, Koen; Carrasco, Maria‐Cecilia; Decaestecker, Ellen; Alonso, Miguel; León‐Tamariz, Fabián; Muylaert, Koenraad
Summary: The tropical Andes has a high density of glacial lakes that are situated in the high‐altitude páramo (3500–4500 m). Ecological information about such lakes is scant despite the fact that these lakes are an important source of water for drinking, irrigation and electricity generation and feed several major tributaries of the Amazon. In this study, we provide data on a survey of 31 lakes in Cajas National Park (Ecuador). Two of the lakes were monitored monthly during one year. In situ nutrient addition experiments were carried out in three of the lakes. Seasonal monitoring in two lakes revealed a thermal stratification of the water column between October and June, with a small temperature difference between epi‐ and hypolimnion (2–3 °C). Oxygen depletion of the hypolimnion towards the end of the stratification period indicated that no complete mixing of the water column occurred during stratification. There was no evidence of depletion of nutrients in the epilimnion or accumulation in the hypolimnion during stratification. There were also no clear seasonal changes in chlorophyll‐ a (Chl‐ a ) concentration nor in phytoplankton community composition in the two lakes. Inputs of dissolved organic carbon (DOC) from the vegetated catchment resulted in high DOC concentrations (median 2.9 mg L −1 ) compared to temperate mountain lakes. Water transparency was relatively low, with a median extinction coefficient for photosynthetic active radiation of 0.50 m −1 and for UV‐B radiation of 10.13 m −1 . Although the thermocline was deep and water transparency was low, estimates of the critical depth for photosynthesis were deeper than the mean water depth in all lakes, suggesting that phytoplankton was not light limited. The phytoplankton community was dominated by chlorophytes (e.g. Oocystis ), diatoms (small Cyclotella spp.) or small colonial cyanobacteria ( Aphanocapsa, Merismopedia ). The zooplankton community was either dominated by large cladocerans and cyclopoid copepods, or by the calanoid copepod Boeckella occidentalis . Total concentrations of phosphorus (P) and nitrogen (N) were comparable to those in temperate mountain lakes (4–35 μg P L −1 and 162–758 μg N L −1 ) while Chl‐ a concentrations were in the lower range (<1 μg L −1 ). A large part of the total nutrient pool consists of dissolved organic N and P that appeared to have a low bioavailability to phytoplankton. The median seston N:P ratio of 44, a positive correlation between Chl‐ a and total P concentration, as well as nutrient addition assays carried out in three lakes all pointed to P limitation of phytoplankton.